Holy Cross Mission, lower Yukon River, Alaska, ca. 1911 - Lomen Bros.
Large field in foreground, with buildings (several multi-storied) and church in background, ca. 1908-1915. Caption on image: Holy Cross Mission. Lomen Bros. PH Coll 328.187